2020
DOI: 10.1097/oi9.0000000000000085
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four posterior approaches of the ankle: A cadaveric study

Abstract: Objectives: The purpose of this study is to provide a detailed comparison of 4 posterior approaches of the ankle: the posteromedial, modified posteromedial (mPM), Achilles tendon-splitting (TS), and posterolateral approaches. Methods: Cadaveric dissections were performed to assess the influence of the medial and lateral retraction forces on the neuro-vascular bundle with suspension scales and to measure the medial and lateral exposed areas of the posterior tibia and tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Proximal zones and points may be useful in revision surgery or chronic Achilles tendon rupture surgery [ 16 , 31 , 41 , 44 ] or in some Achilles tendon lengthening techniques [ 7 , 10 , 19 , 41 ]. The central zones may be useful in acute Achilles pathology surgeries [ 12 , 22 , 35 , 47 ] and distal zones in arthroscopic surgeries [ 2 , 23 , 34 ] or ankle fractures [ 18 , 29 , 33 ]. This new reference line can be easily reproduced intraoperatively (using suture or electric scalpel wire) by the surgeon when planning the approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proximal zones and points may be useful in revision surgery or chronic Achilles tendon rupture surgery [ 16 , 31 , 41 , 44 ] or in some Achilles tendon lengthening techniques [ 7 , 10 , 19 , 41 ]. The central zones may be useful in acute Achilles pathology surgeries [ 12 , 22 , 35 , 47 ] and distal zones in arthroscopic surgeries [ 2 , 23 , 34 ] or ankle fractures [ 18 , 29 , 33 ]. This new reference line can be easily reproduced intraoperatively (using suture or electric scalpel wire) by the surgeon when planning the approach.…”
Section: Discussionmentioning
confidence: 99%
“…Some posterior leg approaches have a high risk of SN injury [ 30 , 47 ]. These approaches are often used in acute [ 12 , 35 , 47 ] or chronic [ 16 , 44 ] Achilles pathology, ankle arthroscopy [ 2 , 23 , 34 ] or ankle fractures [ 18 , 29 , 33 ]. Several authors have attempted to predict the SN location with distance units from the Achilles tendon [ 6 , 10 , 14 , 20 , 46 ] or the lateral malleolus [ 9 , 14 , 15 , 18 , 24 , 30 ], but these units can be altered according to height [ 15 , 20 ], leg length [ 6 ] or body mass index (BMI) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Authors argued that it is needed, because there are no ligamentous insertions that can aid fracture reduction by ligamentotaxis 15 . In a cadaver study, Mitsuzawa et al, compared posteromedial, modified posteromedial (mPM), Achilles tendon-splitting (TS), and posterolateral approaches to the PM 16 .The authors found that the latter, directly endangers the sural nerve and branches of the peroneal artery and does not allow sufficient visualisation of the medial side.The modified posteromedial approach originally described by Assal M 17 , was developed in the interval between the medial neuromuscular bundle and the Achilles tendon. It was found it to be safest and to offer best visualisation, both to the lateral and medial side of the posterior pilon.…”
Section: Discussionmentioning
confidence: 99%
“…Para estas fraturas as abordagens posteriores, como a via posterolateral ou posteromedial, tornaramse mais utilizadas, favorecendo a exposição e a fixação interna. A visibilização do tálus, por exemplo, é importante nas abordagens posteriores, pois permite avaliar um possível dano articular 5 .…”
unclassified